Hubungan antara Budaya Patriarki dengan Sikap Kesetaraan Gender pada Mahasiswi Universitas Negeri Makassar - Irdianti, Irdianti; Zhalsabilla, Annisa; Salinding, Novita; Adnan, Rifqah Athifah Imran (HUMAN: South Asian Journal of Social Studies, 2024)
Abstract. This study, conducted with rigorous methodology, aims to determine whether there is a relationship between patriarchal culture and gender equality. The respondents of the survey are female students from Universitas Negeri Makassar. The method used is a quantitative approach. The population in this study consists of female students from Universitas Negeri Makassar, with a sample size of 42 female students. This research employs a gender equality scale and a patriarchal culture scale. The data analysis techniques used in this study are descriptive statistical methods, correlations, and hypothetical tests to determine the relationship between patriarchal culture and gender equality. Based on the results of the Pearson correlation test using SPSS 25.0 for Windows, it was found that the significance value is 0.002<0.05. A variable is considered to have a relationship if the significance value is <0.05 and does not have a relationship if the significance value is >0.05. Therefore, it can be concluded that there is a relationship between patriarchal culture and gender equality among female students at Universitas Negeri Makassar; thus, H0 is rejected, and Ha is accepted.Keywords: Patriarchal Culture, Gender Equality, Woman